Pengaruh Penerapan Model Pembelajaran Problem Based Learning Terhadap Kemampuan Memecahkan Masalah Pada Pembelajaran Ekonomi Peserta Didik Kelas XI Lintas Minat Ekonomi di SMA Negeri 16 Makassar - Rismayanti Rismayanti; Rahmatullah Rahmatullah; Inanna Inanna; Muhammad Rakib; Muhammad Hasan (Economic Education and Entrepreneurship Journal, 2021)
This study aims to determine the effect of the application of the Problem Based Learning model on the ability to solve problems in economic learning for class XI students across interests in SMA Negeri 16 Makassar.  The research method used was a quasi-experimental design with Nonequivalent (Pretest and Posttest) Control Group Design.  Data collection methods are through tests (pretest and posttest), observation, and documentation.  The number of samples in this study were 72 students, where in the experimental class there were 37 students and 35 students in the control class.  Data analysis used in the form of N-Gain experimental class and control class.  Based on the results of the study, it shows that the Problem Based Learning model variable (independent variable) has an effect on the problem-solving ability variable (the dependent variable).  This is evidenced by the comparison of the experimental class mean value of  0.71 (high) and the control class N-Gain average value of  0.53 (moderate).Keywords: Problem Based Learning Model, Problem Solving Ability